Antimicrobial potency of toothpaste containing gambir (Uncaria gambir) extract - Dewi, Siti Rusdiana Puspa; Handayani, Pudji; Anastasia, Danica; Maulina, Shania Tri (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: The biggest problem in oral health is dental caries and periodontal disease. The way to prevent dental and mouth problems is to keep oral hygiene. One of them is adequate plaque control. Plaque control can be done by brushing teeth and using toothpaste. Currently, many herbal ingredients have been used as antibacterials such as gambir (Uncaria gambir). Gambir mainly contains catechins and tannins, which have the ability to inhibit the growth of bacteria. The purpose of this study was to determine the antimicrobial potential of toothpaste containing gambir (Uncaria gambir). Methods: The total sample was 30, and it divided into three groups. Samples were toothpaste containing ten percent of Uncaria gambir extract, fluoride, placebo toothpaste, Streptococcus mutans (Gram-positive), Phorphyromonas gingivalis (Gram-negative), and Candida albicans. Antimicrobial activity of toothpaste with gambir (Uncaria gambir) extract against microorganisms was observed with the formation of inhibitory zone diameter in agar. Data were analyzed by using SPSS with one-way ANOVA and Tukey test. Results: The results showed that toothpaste containing gambir extract could inhibit the Streptococcus mutans (p<0.05), Phorphyromonas gingivalis (p<0.05), Candida albicans (p<0.05) compared significantly with placebo (p<0.05). Antimicrobial toothpaste containing gambir extract had no different effect from toothpaste containing fluoride. However, toothpaste containing gambir extract had significantly different effect than toothpaste containing fluoride. Conclusion: It can be concluded that toothpaste containing gambir (Uncaria gambir) extract has antimicrobial potential against Streptococcus mutans, Phorphyromonas gingivalis, and Candida albicans. These findings showed that the extract of Uncaria gambir possesses potent antimicrobial activity.